2013
DOI: 10.1111/j.1532-950x.2013.01099.x
|View full text |Cite
|
Sign up to set email alerts
|

Muscle and Tendon Heating Rates with Therapeutic Ultrasound in Horses

Abstract: The SDFT and DDFT are heated to a therapeutic temperature using a frequency of 3.3 MHz and intensity of 1.0 W/cm(2). The epaxial muscles are not heated to a therapeutic temperature using a frequency of 3.3 MHz and an intensity of 1.5 W/cm(2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 22 publications
1
12
1
3
Order By: Relevance
“…In the case of Vasquez et al [18], after the continuous application of US administration, hypertrophy in the gastrocnemius muscle fibers was found to be excessive; it has to be used in pulsed, focused modes to minimize the damage to the surrounding tissues. Montomery et al [19] have concluded that 20 min at 3.3 MHz, 1.5 w / cm 2 density can be used for therapeutic purposes without heating up. There are only a few human studies about the effect of the US on muscle tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of Vasquez et al [18], after the continuous application of US administration, hypertrophy in the gastrocnemius muscle fibers was found to be excessive; it has to be used in pulsed, focused modes to minimize the damage to the surrounding tissues. Montomery et al [19] have concluded that 20 min at 3.3 MHz, 1.5 w / cm 2 density can be used for therapeutic purposes without heating up. There are only a few human studies about the effect of the US on muscle tissue.…”
Section: Discussionmentioning
confidence: 99%
“…However, at the same settings of 3.3 MHz and 1.0 W/cm 2 , there is no change in temperature detected in the epaxial muscles along the spine. 31 In canines, a study looked at Achilles tendon injuries and found that those dogs treated with therapeutic ultrasound (0.5 W/cm 2 ) had improved tendon healing and their return to soundness was more rapid compared with those without therapeutic ultrasound. 32 Therapeutic ultrasound has also been tested in the treatment of induced septic arthritis in donkeys, and those treated with ultrasound therapy had less changes to the joint capsule, synovium, and articular cartilage.…”
Section: Current Researchmentioning
confidence: 98%
“…Devido ao fato de os tecidos dos mamíferos variarem em estrutura, as propriedades térmicas e acústicas dos tecidos diferem entre as espécies. Portanto, é bem provável que o grau de variação de temperatura atingido do tecido, utilizandose um determinado protocolo de US terapêutico, varie entre as espécies (MONTGOMERY et al, 2013). Deve-se levar em consideração o tecido a ser tratado, se tem maior ou menor quantidade de tecido adiposo cobrindo o músculo ou áreas com proeminências ósseas.…”
Section: • Calor Superficialunclassified